The effect of garlic extract and volatile oil on growth of Trichophyton mentagrophytes - Ahmed Humada, Thikra (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was conducted in the College of Medicine- laboratory of microbiology to assess the effect of crude garlic extract and essential volatile oil on growth of Trichophyton mentagrophytes. Antidermatophytic activity of different concentrations of volatile oil, aqueous extract of garlic were investigated in vitro against T. mentagrophytes by using agar dilution technique. The results showed that minimal inhibitory concentration (MIC) of aqueous garlic extract (crude) was 0.5 mg/ ml, while the MIC of essential oil was 0.25 mg/ml